2016
DOI: 10.1108/intr-10-2014-0253
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing pro-social consumer behavior through non-profit organizations

Abstract: Purpose – The purpose of this paper is to analyze the major factors in the intention to adopt pro-social behavior through the internet by dividing them into personal factors and internet factors. Design/methodology/approach – This research uses an empirical model to determine which personal and internet features are significant to consumers’ pro-social concerns. Internet factors may also affect pro-social behavior in addition to personal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 46 publications
(57 reference statements)
0
14
0
1
Order By: Relevance
“…Empathy relies on automatically activated state matching that produces shared representations and similar emotions (Decety and Jackson, 2006); such state matching is prominent wherever humans attempt to cultivate feelings that are more just and compassionate (Gerdes, 2011). Researchers have found that empathy motivates prosocial behaviors (Batson et al, 1995;Eisenberg and Miller, 1987;Murillo et al, 2016), such as donating money to charitable crowdfunding projects (Lee et al, 2014). Hence, cultivating empathy is a main determinant for intention to donate.…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
“…Empathy relies on automatically activated state matching that produces shared representations and similar emotions (Decety and Jackson, 2006); such state matching is prominent wherever humans attempt to cultivate feelings that are more just and compassionate (Gerdes, 2011). Researchers have found that empathy motivates prosocial behaviors (Batson et al, 1995;Eisenberg and Miller, 1987;Murillo et al, 2016), such as donating money to charitable crowdfunding projects (Lee et al, 2014). Hence, cultivating empathy is a main determinant for intention to donate.…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
“…According to Eisenberg and Miller (1987, in Liu et al , 2018), empathy is an affective state that comes from understanding others’ states or emotional conditions. It is also defined by Hoffman (2001) and Batson (2014) as affective responses that are identical or similar to what other people feel or feelings that might be expected in a particular context (Murillo et al , 2016). Studies suggested that individuals are encouraged to donate because they feel empathy with certain projects (Gerber et al , 2012).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Previous studies propose that cultural orientation also plays a central role in technology-related behaviors (e.g. Tam and Oliveira, 2017; Agag and El-Masry, 2016; Elbeltagi and Agag, 2016; Murillo et al , 2016; Kim and Jeong, 2015; Zhao, 2011; Frost et al , 2010). For example, researchers have found that cultural orientations have a significant effect in internet use (Chen and Nath, 2016; Nath and Murthy, 2004), e-commerce (e.g.…”
Section: Introductionmentioning
confidence: 99%